Kontribusi Quality of Nursing Work Life (QNWL) dan Kepuasan Kerja terhadap Kinerja Perawat Rumah Sakit - Achmad Dwityanto Oktaviansyah; Prabandari Puspita Ardyanto; Zalfa Dhanya Enkaputri (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2026)
The performance of hospital nurses is greatly influenced by the quality of the work environment. Quality of Nursing Work Life (QNWL) reflects the level of comfort, well-being, and support that nurses experience in the workplace. In addition, job satisfaction plays a crucial role in motivating nurses to perform at their best. This study examines the relationship between QNWL job satisfaction, and nurse performance. QNWL refers to the level of comfort, well-being, and support experienced by nurses in their work environment. Meanwhile, job satisfaction is a key factor that drives nurses to perform their work optimally. This study employed a quantitative correlational approach, involving 95 nurses from X Hospital in Surakarta, selected through purposive sampling. Nurses’ performance, job satisfaction, and QNWL were measured using standardized scales and analyzed via multiple linear regression. The results revealed a significant relationship between QNWL and job satisfaction with nurses’ performance (R = 0.584, F = 23.847, p = 0.000). Specifically, QNWL had a positive correlation with nursing performance (r = 0.517, p = 0.000), and job satisfaction also had a positive correlation with nursing performance (r = 0.553, p = 0.000). These results indicate that QNWL and job satisfaction significantly contribute to improved nursing performance.